The Land Snails of Carter Caves State Park, Carter County, Kentucky - Ralph W. Taylor; Clement L. Counts; Susan L. Stryker (Hello World!, 1977)
Hubricht (1968) noted that a comprehensive treatment of the land snails of Kentucky had yet to appear in the literature. In his attempt to rectify the problem, he reviewed specimens which were a part of his own collections to provide the most complete checklist of Kentucky snails yet to appear at that time (Hubricht, 1968). His collections were, however, quite scanty for some counties. Branson and Batch (1971) provided a similar list of Kentucky Mollusca which filled in some of the distributional gaps of Hubricht. In an earlier paper by Branson and Batch (1968) a checklist of 43 species of land snails was compiled for Pine and Big Black Mountains of southern Kentucky. The regional approach to examination of molluscan fauna is prevalent in the literature of Kentucky land snails (Price, 1900; Hubricht, 1964; Bickel, 1967). This method presents problems to future investigators of the fauna of a geopolitical area. Difficulty arises in synthesizing many reports into a whole, but one advantage is that more complete collection of a specific area allows a more accurate distributional pattern to be delineated. The present paper is a report on the land snails of Carter Caves State Park, Carter County, Kentucky which provides additional distributional data for eastern Kentucky: an area of the state either poorly collected or generally ignored in previous studies.